Workshop Penyusunan Soal Asessmen Berbasis AKM Literasi Bagi Guru–Guru SMK Hasyim Asy’ari Mojokerto - Wawan Hermawan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This service seeks to provide understanding to teachers to improve their competence in preparing literacy AKM-based assessment questions. The stages of this service activity include: delivering material, discussing the material, compiling literacy AKM-based assessment questions, and evaluation. Community service activities are carried out using a workshop type. This service activity uses lecture, discussion and exercise methods. The lecture method is carried out by providing material to teachers regarding the preparation of literacy AKM-based assessment questions. Discussions and exercises are carried out by applying the material provided by the presenter. In the practical training process, teachers are asked to prepare literacy AKM-based assessment questions based on the material that has been presented. The results of service activities in the form of a workshop on making literacy AKM-based assessment questions for teachers at Hasyim Asyari Vocational School, Mojokerto, have had an impact on increasing teacher competency and professionalism, especially in making literacy AKM-based assessment questions.